How do forensic clinicians decide?: a Delphi approach to identify domains commonly used in forensic juvenile treatment planning - Hillege, Sanne L. (International journal of offender therapy and comparative criminology, 2018)
Adolescents in forensic care display wide varieties of complex psychiatric, psychological, and contextual problems. Based on large amounts of information, clinicians need to consider, integrate, and prioritize these offender characteristics to construct individual treatment trajectories. So far, scientific knowledge on how these treatment decisions take place is scarce. Current study uses a qualitative design for detecting implicit knowledge of clinicians on which offender characteristics they consider while making treatment decisions. Using the Delphi method, 34 experienced clinicians working in forensic care facilities in the Netherlands were asked about the most important domains of offender characteristics that influence their treatment planning. Eight domains were identified as being crucial in treatment planning: Mental health problems, Personal characteristics, Family, Offense, Motivation, Treatment, School/Work/Housing, and Peers/Spare time. Based on current results, focus on a broad spectrum of individual and contextual characteristics is recommended. Moreover, protective factors and comorbid problems on multiple domains should be considered.